PHYSICAL-TECHNOLOGICAL ASPECTS OF SIMULATION OF SILICON AND GALLIUM ARSENIDE LOW-TEMPERATURE EPITAXIAL LAYERED STRUCTURES - Новосядлий, Степан Петрович; Терлецький, Андрій Іванович; Фрик, Оксана Богданівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
It was considered the questions of the growing technology of monosilicon and gallium arsenide epitaxial layers, which are used to create components of large integrated circuits. The processes of low-temperature epitaxy and their models in the formation of sub-micron structures of LSI both on mono-Si and on GaAs have been investigated. This technology allows for the formation of GaAs structures on Si-substrates.